Punishing Latina/o Youth: School Justice, Fairness, Order, Dropping Out, and Gender Disparities. (February 2017) - Peguero, Anthony A.; Bondy, Jennifer M.; Shekarkhar, Zahra
Although Latina/o youth are one the fastest growing segments of the U.S. population, they face a number of educational hurdles, such as disproportionate school punishment and increased risk of dropping out of high school. This topic is particularly relevant today in the midst of the current social, political, and economic debate over the "school-to-prison pipeline." This study draws from the Educational Longitudinal Study and utilizes multilevel modeling to analyze the relationships between school justice, fairness, order, dropping out, and gender disparities for 1, 800 Latina/o and 6, 300 White public school students. Findings suggest that school punishment is contributing to Latina/o youth dropping out; however, it is also evident that improving school justice and fairness can ameliorate the risk of dropping out for Latina/o youth. The significance and implications of justice, fairness, and order for Latina/o youth within the United States school system are discussed more generally.